2021
DOI: 10.1007/s00259-021-05282-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of long axial field of view PET/CT: a head-to-head intra-individual comparison of the Biograph Vision Quadra with the Biograph Vision PET/CT

Abstract: Purpose To investigate the performance of the new long axial field-of-view (LAFOV) Biograph Vision Quadra PET/CT and a standard axial field-of-view (SAFOV) Biograph Vision 600 PET/CT (both: Siemens Healthineers) system using an intra-patient comparison. Methods Forty-four patients undergoing routine oncological PET/CT were prospectively included and underwent a same-day dual-scanning protocol following a single administration of either 18F-FDG (n = 20), 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
149
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(159 citation statements)
references
References 28 publications
5
149
2
3
Order By: Relevance
“…The brain-heart axis is further implicated in post-stroke cardiovascular complications known as the stroke-heart syndrome, sudden cardiac death and the Takotsubo syndrome, amongst other neurocardiogenic syndromes. In the early 1990s, a dynamic [ 15 O]H 2 O PET brain study identified the central nervous pathways of angina pectoris, highlighting the interplay between the brain and the heart in such patients [29]. One other obvious example would be the emerging evidence of the role of acute myocardial infarction (MI) that triggers both local and systemic inflammatory responses.…”
Section: Organ Axesmentioning
confidence: 99%
See 2 more Smart Citations
“…The brain-heart axis is further implicated in post-stroke cardiovascular complications known as the stroke-heart syndrome, sudden cardiac death and the Takotsubo syndrome, amongst other neurocardiogenic syndromes. In the early 1990s, a dynamic [ 15 O]H 2 O PET brain study identified the central nervous pathways of angina pectoris, highlighting the interplay between the brain and the heart in such patients [29]. One other obvious example would be the emerging evidence of the role of acute myocardial infarction (MI) that triggers both local and systemic inflammatory responses.…”
Section: Organ Axesmentioning
confidence: 99%
“…Indeed, impressive dynamic data from the nearly 2-m-long PET scanner at the University of California, Davis, have indicated that the arterial input function could be measured with sufficiently high rates immediately after radiotracer injection, thus providing a new potential for translating kinetic analysis in clinical practice [37]. For some tracers, such as [ 18 F]FDG and [ 15 O]H 2 O, arterial whole blood concentrations are sufficient for determining the arterial input function. For most other tracers, however, the metabolite-corrected arterial plasma curve is needed as input function, which means that arterial samples are still required to determine the fraction of parent compound.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the July issue of European Journal of Nuclear Medicine and Molecular Imaging , a superbly designed and executed study on the first clinical implementation of a LAFOV PET/CT scanner was reported by Dr. Rominger and colleagues from Bern University Hospital, University of Bern, Switzerland [ 5 ]. This is a prospective, non-randomized, dual-arm crossover, comparative imaging study with a clearly stated hypothesis and inclusion/exclusion criteria.…”
mentioning
confidence: 99%
“…Two PET/CT systems from Siemens Healthineers were compared in this study [ 5 ]. One is the first Biograph Vision Quadra LAFOV PET/CT system (axial FOV 106 cm), with a sensitivity of ≥ 70 cps/kBq and a time resolution of 219 ps in ultra-high sensitivity mode.…”
mentioning
confidence: 99%